2011
DOI: 10.9738/cc82.1
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholangiocarcinoma Arising 33 Years After Excision of a Choledochal Cyst: Report of a Case

Abstract: We report a case of intrahepatic cholangiocarcinoma arising 33 years after excision of a choledochal cyst. A 61-year-old woman was admitted to our hospital complaining of fever. Thirty-three years ago she had undergone extrahepatic choledochal cystectomy and choledochojejunostomy for a choledochal cyst. Computed tomography showed a tumor in the anterior segment of the liver, extending to the posterior and medial segments and the right portal vein. Intrahepatic biliary stones were seen in the bile ducts. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It is recommended that the extrahepatic bile duct be resected near the level of the pancreatobiliary junction with a wide hepaticoenterostomy at the hilum of the liver to avoid these complications . Development of biliary cancer following choledochal cyst resection, cholangitis, and intrahepatic stones have been noted predominantly in types I and IV‐A cysts in several studies …”
Section: Choledochal Cystsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended that the extrahepatic bile duct be resected near the level of the pancreatobiliary junction with a wide hepaticoenterostomy at the hilum of the liver to avoid these complications . Development of biliary cancer following choledochal cyst resection, cholangitis, and intrahepatic stones have been noted predominantly in types I and IV‐A cysts in several studies …”
Section: Choledochal Cystsmentioning
confidence: 99%
“…22 Development of biliary cancer following choledochal cyst resection, cholangitis, and intrahepatic stones have been noted predominantly in types I and IV-A cysts in several studies. 12,15,22,27 Proposed timeline: From birth to transition/transfer. Children with CDCs are typically diagnosed within the first decade of life.…”
Section: Choledochal Cystsmentioning
confidence: 99%
“…[57][58][59] In several series, all patients with malignancy following cyst excision were diagnosed with adenocarcinoma (►Table 1). 28,29,38,40,42,58 Recently, Ng et al reported on the rare case of metachronous cholangiocarcinoma 13 years postresection and Tajiri et al described a mucinous cystadenoma of the pancreas 17 years following gallbladder resection due to choledochal cyst. 57,60 Otani et al described a rare case of a bile duct schwannoma developing in remnant choledochal cyst.…”
Section: Histological Findingsmentioning
confidence: 99%
“…[7] Technically, cyst excision is the main step to diminish the risk for cancer development, and must be performed when it is possible. [3] Unfortunately, a cholangiocarcinoma may arise even after the cyst excision, as described by Nishiyama et al [8] The surgical strategy depends on the type of the cyst. For the Type I cyst, complete excision of the cyst is usually feasible and Roux-en-Y hepaticojejunostomy is the preferable reconstruction technique.…”
Section: Discussionmentioning
confidence: 99%